The Cannonball Run - Needham, Hal, 1931-2013; Yates, Brock, 1933-2016; Ruddy, Albert S., 1930-2024; Reynolds, Burt; Fawcett, Farrah, 1947-2009; Moore, Roger, 1927-2017; DeLuise, Dom; Martin, Dean, 1917-1995; Davis, Sammy, Jr., 1925-1990; Barbeau, Adrienne, 1945-; Farr, Jamie, 1934-; Bradshaw, Terry; et al. ([New York, NY] : Home Box Office ; Burbank, CA : Distributed by Warner Home Video, 2009)
A mad-cap, illegal cross country race is the focus of this car chase comedy.
Title from container.
Originally released as a motion picture in 1981.
Special features include audio commentary with director and producer, cast and crew bios.
New DVD 2023 Summer.
Executive producer, Raymond Chow.
Burt Reynolds, Farrah Fawcett, Roger Moore, Dom DeLuise, Dean Martin, Sammy Davis, Jr., Adrienne Barbeau, Jamie Farr, Terry Bradshaw, Mel Tillis, Jackie Chan, Michael Hui.
Keywords: Automobile racing -- Drama; Motorsports -- Drama; Films for the hearing impaired; Video recordings; Drama; Feature films; Comedy films